PENGARUH LINGKUNGAN KERJA, BUDAYA ORGANISASI, KEPEMIMPINAN TERHADAP KINERJA (Studi pada Pegawai Kecamatan Sidorejo Kota Salatiga) - Widodo, Tri (AMONG MAKARTI, 2010)
Abstract The purpose of this research is to know the influence of working sphere, organization culture, and leadership towards employe’s,s working performance at Kecamatan Sidorejo Kota Salatiga. Data for this research was collected using a questionnaire which is spread to all employee at Kecamatan Sidorejo Kota Salatiga for thr amount of 60 peoples. To answers research questions, the collected data is analyze using multiple regression test which is include t-test ( parsially test ) and F-test ( simultaneous test ). The result of this research shows that : (1) There is a positif and significance influence of working sphere towards employee’s working performance at Kecamatan Sidorejo Kota Salatiga, (2) There is a positif and significance influence of organization culture towards employee’s working performance at Kecamatan Sidorejo Kota Salatiga, (3) There is a positif and significance influence of leadership towards employee’s working performance at Kecamatan Sidorejo Kota Salatiga,(4) Simultaneously there is a positif and significance influence of working sphere, organization culture, and leadership towards employee’s working performance at Kecamatan Sidorejo Kota Salatiga. According to the result of this research, strongly suggested to all employee at Kecamatan Sidorejo Kota Salatiga to increase and improve their creativity and motivate themselves to achieve higher performance, and working togheter with all elements of organization to create a positif working sphere. To the leader of organization is suggested to become a positif example for employee, and establish a positif and condusive working sphere so the employee’s perception towards working sphere, organization culture, and leadership will improve time by time. In the end all that variables are needed to improve employee’s working performance. Keywords : working sphere, organization culture, leadership, working performance